Situation Report: Hungary, 20 June 1973 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Demographic Policy Objectives Arouse Public Interest Reduced Work Week for Civil Servants Western Imports Needed for Agricultural Mechanization Program Austrian Minister of Agriculture and Forestry Visits Hungary June Session of the National Assembly